2005
DOI: 10.1105/tpc.105.032185
|View full text |Cite
|
Sign up to set email alerts
|

Antiquity of MicroRNAs and Their Targets in Land Plants

Abstract: MicroRNAs (miRNAs) affect the morphology of flowering plants by the posttranscriptional regulation of genes involved in critical developmental events. Understanding the spatial and temporal dynamics of miRNA activity during development is therefore central for understanding miRNA functions. We describe a microarray suitable for detection of plant miRNAs. Profiling of Arabidopsis thaliana miRNAs during normal development extends previous expression analyses, highlighting differential expression of miRNA familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
430
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(468 citation statements)
references
References 60 publications
32
430
0
6
Order By: Relevance
“…The evolution and conservation of plant miRNAs has been the subject of significant investigation (Axtell and Bartel, 2005;Zhang et al, 2006a;Axtell and Bowman, 2008). In this study we have identified multiple highly conserved plant miRNAs in Aquilegia as well as miRNA families that have a more disjointed phylogenetic distribution.…”
mentioning
confidence: 73%
“…The evolution and conservation of plant miRNAs has been the subject of significant investigation (Axtell and Bartel, 2005;Zhang et al, 2006a;Axtell and Bowman, 2008). In this study we have identified multiple highly conserved plant miRNAs in Aquilegia as well as miRNA families that have a more disjointed phylogenetic distribution.…”
mentioning
confidence: 73%
“…AP2-like genes containing putative miR172 target sites are conserved in eudicots, monocots and early land plants (Aukerman and Sakai 2003;Axtell and Bartel 2005). It is thus conceivable that transgenic expression of Arabidopsis miR172 and AP2 in heterologous angiosperm species would elicit similar developmental phenotypes as those previously uncovered in Arabidopsis (Aukerman and Sakai 2003;Chen 2004).…”
Section: Introductionmentioning
confidence: 87%
“…Several families of microRNAs (miRNAs) have been found in green plants ranging from algae, mosses, ferns, gymnosperms and angiosperms (Floyd and Bowman, 2004;Arazi et al, 2005;Axtell and Bartel, 2005;Molnár et al, 2007;Zhang et al, 2006;Zhao et al, 2007) suggesting that the regulation by miRNA is ancient in origin. At least 88 annotated miRNA families have been identified in the moss P. patens and 44 in the lycopod Selaginella moellendorffii (Axtell et al, 2007;Fattash et al, 2007).…”
Section: Bryophytes As An Ancient Lineage May Have Retained Many Novementioning
confidence: 99%